Penerapan Terapi Distraksi Untuk Menurunkan Kecemasan Pada Pasien Menjalani Kemoterapi Di Rumah Sakit - Alviatun Nayiroh; Rima Berliana Putri; Ricky Riyanto Iksan (Akademi Keperawatan Yarsi Samarinda, 2026)
affect patient comfort and compliance with therapy. Distraction therapy is a non-pharmacological intervention that aims to divert patient attention to reduce anxiety and pain. Objective: This EBN is to determine the effectiveness of distraction therapy in reducing patient anxiety levels compared to patients who did not receive intervention. Method: EBN data were measured before and after the intervention using a standard scale. Analysis was conducted to compare anxiety levels between the two groups. Results: Before the intervention, anxiety levels in both groups were relatively similar and did not differ statistically significantly (p = 0.210). After being given distraction therapy, the intervention group showed a significant decrease in anxiety with a mean value = 12.3 and SD = 1.15, compared to the control group with a mean = 27.5 and SD = 1.41. The analysis showed a p-value = 0.018 (<0.05), indicating a significant difference between the two groups. Conclusion: Distraction therapy has been proven effective in reducing patient anxiety levels during medical procedures. This intervention can be a safe and effective non-pharmacological strategy to improve patient comfort and promote a more positive care experience.